Desenvolvimento, Modernidade e Meio Ambiente: um estudo a partir de um campo a sociologia do desenvolvimento - SOARES, Sarah Pereira (2011)
The issue of development, during the years 50 and 60, was widely discussed in the social sciences and was addressed by several authors from different perspectives. Today, the human and social development is thought from the perspective of a new social and economic context. However, it is believed that one cannot disregard the interpretive strength of the concepts developed by theorists of this period. In this sense, this paper set out to study development, modernity and the environment from the intellectual production of the sociology of development. With that, we tried to reflect about the concepts formulated by different authors to explain the development, whose production results of a field of knowledge in accordance with to the social, economic and cultural conditions which bring about its emergence and also rescue the present time of this literature, that is, have understand of how the issues involved in the issue of development, such as concern for the environment were already present in this intellectual production.